БОЛЬ В ПЛЕЧЕЛОПАТОЧНОЙ ОБЛАСТИ: КЛИНИЧЕСКИЕ АСПЕКТЫ ДИАГНОСТИКИ И ЛЕЧЕНИЯ - А. А. Фирсов; В. И. Шмырёв (SINAPS LLC, 2014)
The problem of pain in the glenohumeral region is an urgent problem for many decades. The article describes the clinical aspects of diagnosis and treatment of pain in the glenohumeral region, particularly in the application of conservative treatment of pain along with nonsteroidal anti-inflammatory drugs neurotropic complexes Milgamma.